P151 Polyp detection using dye spray chromoendoscopy in patients with serrated polyposis syndrome. (19th June 2022) - Bowman, Amelia; Murphy, Aisling; Bailey, Adam; Bird-Lieberman, Elizabeth; Leedham, Simon; East, James; Biswas, Sujata
Abstract : Introduction: Patients with Serrated Polyposis Syndrome (SPS) require regular colonoscopic surveillance to reduce polyp burden and subsequent colorectal cancer. It is not established whether the use of dye spray chromoendoscopy improves serrated polyp detection and BSG guidelines do not definitively recommend it in SPS surveillance 1 . Methods: A database of patients with SPS according to the WHO 2019 criteria 2 was established at Oxford University Hospitals NHS Trust. Data collection began in 2010 and in total there are 182 SPS patients. The most recent colonoscopy for each patient was analysed. Patient characteristics, adequacy of bowel preparation, use of dye spray and polyp detection were retrospectively measured. Statistical analysis was performed using the chi-squared test. Results: 182 colonoscopies were performed from 2016 to 2021. 84/182 patients were male (46.2%) and the age range at the time of colonoscopy was 32-86 years. Bowel preparation was recorded as adequate in 175/182 procedures (96%) and indigo carmine dye spray was used in 92/182 patients (50.5%). Overall serrated polyps were identified in 145/182 procedures (79.7%). Right sided polyps, either serrated or adenomatous, were identified in 119/182 procedures (65.4%). Serrated polyps were detected in 79/92 (85.9%) of dye spray procedures vs 66/90 (73.3%) of white light (WLI) procedures (p=0.04). Right sided polyps were detected in 65/92 (70.7%) of dye spray procedures vs 54/90 (60.0%) of WLI procedures (p=0.13). Conclusions: In this cohort dye spray chromoendoscopy significantly enhanced detection of serrated polyps and non-significantly improved detection of right-sided polyps. We therefore recommend that chromoendoscopy is considered in SPS surveillance. References: Monahan KJ, Bradshaw N, Dolwani S et al. Guidelines for the management of hereditary colorectal cancer from the British Society of Gastroenterology (BSG)/Association of Coloproctology of Great Britain and Ireland (ACPGBI)/United Kingdom Cancer Genetics Group (UKCGG). Gut 2020;69(3):411-444. Rosty C, Brosens LAA, Nagtegaal ID. Serrated Polyposis. WHO Classification of Tumours. Digestive System Tumours, 2019.